IDENTIFIKASI FORMALIN PADA IKAN ASIN YANG DIJUAL DI KAWASAN PANTAI TELUK PENYU KABUPATEN CILACAP - Wardani, Rossy Indah; Mulasari, Surahma Asti (Universitas Ahmad Dahlan, 2016)
Background: Food additives are substances intentionally added to food to affect the nature of the food one is formalin. Formalin in food could have a negative impact on public health. Preliminary studies showed that salted fish identified positively to contain formalin. The purpose of this study was to determine the formaldehyde content in the salted fish sold in the Gulf Coast Region Penyu Cilacap. Method: The study was descriptive qualitative research with laboratory approach. Primary data were obtained from laboratory tests on interviews with anchovies and salted fish traders.. Respondents were 23 traders anchovies in the coastal region of Penyu Gulf, Cilacap district. The instrument of this sutdy were the questionnaire to measure the level of knowledge and attitudes of respondents. This study used 13 samples of salted fish. Results: This study used 13 samples of salted fish. The results showed that there is one sample of dried fish (7.69%) positively identified to contain formalin. In addition, the level of knowledge of 15 respondents are still in the category is not well in spite of the attitude shown by the 20 respondents have either. Source anchovies that are sold at most be obtained by purchase from manufacturers found in 13 respondents while the way to buy and own production of each found as many as five respondents. Conclusion: One sample of salted fish sold in the Penyu Gulf, Cilacap district have positively identified to contain formalin. The level of knowledge respondents categorized not good when the respondents' attitudes toward the use of formaldehyde has been good. Therefore, a tight control by the parties involved in minimizing the use of formaldehyde as well as socialization formaldehyde hazard to health.